Analisa Eksploratif Pengaruh Jumlah Subscriber dan Jumlah Upload terhadap Penghasilan Youtuber - Lusi Zafriana (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
YouTube has become a critical platform for individuals and organizations to rapidly and broadly reach audiences and generate income. Although the current trend suggests that the YouTube platform holds significant potential in generating substantial revenue, it is essential to identify and deeply understand various interacting factors. This research aims to comprehend the influence of the number of subscribers and the number of uploads on a YouTuber's monthly income. Through exploratory and inferential data analysis, this study concludes that the number of subscribers positively correlates with a YouTuber's monthly income, and there is no definitive correlation between the number of uploads and monthly earnings. The results of this study indicate that to achieve financial goals through the YouTube platform, YouTubers need to consider a range of factors, not limited to the number of subscribers and the amount of uploads. This research provides insights for YouTubers and other researchers to better understand the existence of other factors that influence a YouTuber's monthly income.